Detecting and explaining technological innovation in prehistory - Spataro, Michela; Furholt, Martin 1975- (Sidestone Press, 2020)
Technology refers to any set of standardised procedures for transforming raw materials into finished products. Innovation consists of any change in technology which has tangible and lasting effect on human practices, whether or not it provides utilitarian advantages. Prehistoric societies were never static, but the tempo of innovation occasionally increased to the point that we can refer to transformation taking place. Prehistorians must therefore identify factors promoting or hindering innovation.00This volume stems from an international workshop, organised by the Collaborative Research Centre 1266 'Scales of Transformation' at Kiel University in November 2017. The meeting challenged its participants to detect and explain technological change in the past and its role in transformation processes, using archaeological and ethnographic case studies. The papers draw mainly on examples from prehistoric Europe, but case-studies from Iran, the Indus Valley, and contemporary central America are also included. The authors adopt several perspectives, including cultural-historical, economic, environmental, demographic, functional, and agent-based approaches.
Der vollständige Titel der Reihe "Scales of transformation in Prehistoric and Archaic societies" erscheint auf dem Umschlag
Keywords: Vor- und Frühgeschichte; Technische Innovation; Konferenzschrift -- 2017 -- Kiel